Asymmetric hydrophosphination of cyano-functionalised 1, 3-diphenylphosphine and catalytic asymmetric hydrophosphination of enones with diphenylphosphines - Lee, Zhi Yi (2012)
Over the past decades, the design, synthesis of chiral diphosphines in the field of asymmetric catalysis has grown tremendously due to its widespread applications[1, 2]. The optical pure diphosphines containing the 1,3-bis(diphenylphosphino)propane backbone have widespread applications as bidentate ligands in transition metal catalyzed asymmetric reactions[3-15]. Hence, the development of new methods or strategies for the synthesis of enantiomerically pure diphosphines ligand continues to be an important topic in chemical research. On the other hand, organometallic complexes can act as efficient reaction promoters, by means of coordination; they could protect the phosphine substrate from oxidation during addition reaction. When the chiral auxiliaries were incorporated with these organometallic reagent, they also provide the protocol to synthesize chiral version of the bidentate diphosphine ligand.[16-19]